1990
DOI: 10.1212/wnl.40.8.1203
|View full text |Cite
|
Sign up to set email alerts
|

Cortical‐basal ganglionic degeneration

Abstract: Article abstract-We report our experience with 15 patients believed to have cortical-basal ganglionic degeneration. The clinical picture is distinctive, comprising features referable to both cortical and basal ganglionic dysfunction. Characteristic manifestations include cortical sensory loss, focal reflex myoclonus, "alien limb" phenomena, apraxia, rigidity and akinesia, a postural-action tremor, limb dystonia, hyperreflexia, and postural instability. The asymmetry of symptoms and signs is often striking. Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
166
3
6

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(182 citation statements)
references
References 10 publications
7
166
3
6
Order By: Relevance
“…Symmetric onset of motor symptoms is characteristic, in contrast to PD and corticobasal degeneration [30, 31] where the signs are typically asymmetric and even unilateral. Although symmetry is not invariant, unilateral or predominantly unilateral motor deficits suggest a diagnosis other than PSP [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetric onset of motor symptoms is characteristic, in contrast to PD and corticobasal degeneration [30, 31] where the signs are typically asymmetric and even unilateral. Although symmetry is not invariant, unilateral or predominantly unilateral motor deficits suggest a diagnosis other than PSP [13].…”
Section: Discussionmentioning
confidence: 99%
“…Down-gaze palsy is considered specific for PSP (although it occurs in corticobasal degeneration [30, 31] and, uncommonly, in other conditions [5]). Supranuclear gaze palsy was present in all cases in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It was initially reported as "corticodentatonigral degeneration with neuronal achromasia." 3 Patients typically present a slowly progressive asymmetric akinetic-rigid syndrome commonly affecting the upper extremities.…”
mentioning
confidence: 99%
“…Although the existing diagnostic criteria for CBD are not formally validated and definitive diagnosis is made only after neuropathological confirmation, Watts et al suggested akinesia, rigidity, postural or gait disturbance, postural and action tremor, alien limb phenomenon, dystonia, myoclonus as the major criteria for the disease diagnosis and choreoathetosis, dementia, blepharospasm, and cerebellar signs (like supranuclear gaze abnormalities) as the minor ones [4,5]. According to Riley et al, the clinical manifestations can be separated into those that appear as a result of basal ganglia impairment (eg akinesia, rigidity, dystonia, athetosis, postural instability), to those that have a cerebral cortex origin (eg alien limb phenomenon caused by cortical sensory loss, cognitive decline) and other features such as a postural-action tremor that often evolves to myoclonus, hyperreflexia, impaired ocular and eyelid motility, dysarthria and dysphagia [6]. The L-dopa response is poor.…”
Section: Discussionmentioning
confidence: 99%
“…No abnormalities appear on conventional EEG, at least at the disease onset, although some patients may present a unilateral slowing [22][23][24]. J. Vion-Dury et al found significant modification of brain electrical activity in CBD.…”
Section: Discussionmentioning
confidence: 99%